THE CORRELATION BETWEEN EFL COLLEGE STUDENTS’ LARGE CLASSES AND THEIR ACADEMIC PERFORMANCE - Al-Obaydi, Liqaa Habeb; AL-Bahadli, Khansaa Hassan (PEOPLE: International Journal of Social Sciences, 2017)
Large classes are a problem that faces specifically educational institutions which provide a high quality type of education to its students. According to this study, the term large class applies usually to classes with more than 60 students. This study shed the light on the correlation between class size and students’ academic performance as one of the contemporary problems that need to be under investigation. It aims at determining the correlation between large class size and academic performance of students, and determining the highly percentages problems determined by students in relation to large classes. The population of this study is university students, and the sample consists of eighty students as a main sample. The researchers construct scaled questionnaire to measure large class size problematic areas to correlate it with students’ final rates that are dependent by the researchers as their academic performance. Person correlation coefficient was used to find this relation. Initial correlation analyses indicate a negative relationship between class size and students’ academic performance. In the light of the results obtained, recommendations which are concerned with teachers and students are put forward.